KONSENTRASI MINYAK SAWIT MENTAH (CPO) DI KAWASAN PESISIR DUMAI PROVINSI RIAU - Hayatun Nufus (Universitas Teuku Umar, 2018)
Dumai waters was categorized as being prone to oil spills, because the dominant industrial activities in the area, is crude palm oil (CPO) industry. This study aimed to determine the level of oil and fat pollution in Dumai Coastal Area of Riau Province. The determination of CPO in water and sediment was carried out through the tests in the laboratory. CPO concentration in Dumai Coastal Waters was still in the category of being unpolluted and it was safe for the environment. Keywords: Dumai Coastal Waters, CPO, oil and fat